Mulheres negras empreendedoras no Brasil: suas barreiras e comportamento de superação para empreender - Aguiar, Heraldo Márcio de (2022)
The societies social and main structures have consolidated an understanding that entrepreneurship is sponsored by traditional majority groups, that is, white color and male gender. However, reality and literature prove that minorities undertake mostly as a response to the difficulties imposed by unequal and discriminatory societies. Being included in two minority groups at the same time, women and black women establish their enterprises in a social environment full of difficulties resulting not only from the business environment itself, but also from gender and race discrimination. Research Question: how do black Brazilian women entrepreneurs face the barriers and develop overcoming behaviors? General objective: to investigate how black Brazilian women entrepreneurs overcome the barriers undergone and develop behaviors to overcome difficulties. Relevance: This study eliminates a gap that persists in studies of entrepreneurship by minorities in Brazil, that is, the gap to investigate black women in isolation, as a specific object of studies within the field. This study focuses only on black women and is in line with international research that already has a considerable body of studies in this group of entrepreneurs. Methodology: This research was developed with qualitative methods, exploratory and descriptive in nature. The research techniques adopted were the performance of a focus group with seven participants and the conduction of individual interviews with five entrepreneurs, with a view of collecting, from the narratives of the participants, information relevant to the entrepreneurial reality, their barriers and overcoming behaviors. Results: identification of business threats that are specific to black entrepreneurs in Brazil and how they face barriers and difficulties. The study allowed an important theoretical and empirical survey of the constructs addressed. It was possible to identify the challenges faced by black entrepreneurs, consisting of eleven categories: financial, racism, prejudice for being black woman, reconciliation between family vs. work, time management, machismo and sexism, loss of beloved ones, execution of business contracts, lack of support from the black community, articulation of the black community, distribution of products and penetration of products into the market. Their ways of overcoming difficulties were found to be courage, recognition, perseverance, family, ancestry, inner strengthening, altruism, do what they like to do, psychological strengthening, relationships, prayer and gratitude, empowerment, relationships, career, organization, and planning, thus using the affective and cognitive for the overcoming. From this knowledge, future studies will allow the construction of comparative scenarios between Brazilian states and countries to deepen more and more the awareness of the influence of social structures and public social-and-economic-development policies on the entrepreneurship by minorities. Potential theoretical and methodological contributions: this research contributes to the interdisciplinary character of studies in entrepreneurship from the analysis of the phenomenon through the perspective of stereotype threat, a concept still little studied in the field of entrepreneurship in Brazil. In addition, the integration between the social context and the psychological approach through the study of behaviors expands the contribution of this study. Potential applications of the results and possible extension of the research: the results may contribute to the development of public, educational, social, and cultural policies and develop actions of anti-discriminatory citizenship that may favor minorities wishing to undertake.